Isometric Force-Time Curve Assessment: Accuracy, Precision, and Repeatability of a Mobile Application and Portable and Lightweight Device - Dario Santos; Alfredo Bravo-Sánchez; Leonardo Alexandre Peyré-Tartaruga; Franco Simini; Rodrigo Zacca (MDPI AG, 2024)
Strength assessment is one of the main fields in sports performance, physical rehabilitation, physical activity, and health. We aimed to compare maximal voluntary isometric contractions (MVICs) and paired voluntary isometric contractions (VICs) of knee extensors between an isokinetic dynamometer (BIODEX) and a portable and lightweight device (DINABANG). From 19 volunteers (age: 28.7 ± 7 years; body mass: 72 ± 10 kg; and height: 173 ± 7 cm) we obtained 114 paired MVIC measures and, from the force-time curves of these repetitions, 22,507 paired VIC measures of knee extensors. We observed "excellent" repeatability for MVICs (ICC:1.00; p < 0.001) between BIODEX (247 ± 79.5 Nm) and DINABANG (247 ± 74.8 Nm), with "trivial" effect (mean difference: 0.12 Nm (0.02%); 95%CI: −0.13 to 0.23 Nm; p = 0.606; d = 0.048). Bland-Altman plots revealed high accuracy for MVIC (bias: 0.12 Nm) and consistent distribution (precision) inside the limits of agreement (−4.81 to 5.06 Nm) and respective 95%CI. "Excellent" repeatability was also observed for VICs (ICC:1.00; p < 0.001) between BIODEX (219 ± 84.1 Nm) and DINABANG (218 ± 84.0 Nm), with "trivial" effect (0.24 Nm (0.11%); 0.08 to 0.11 Nm; p < 0.001; d = 0.100). Bland-Altman plots revealed high accuracy for VICs (bias: 0.24 Nm) and consistent distribution (precision) inside the limits of agreement (−4.5 to 4.9 Nm) and respective 95%CI. DINABANG is accurate, precise, and reliable in torque measurement.